The Influence of Erotic Stimulation on Brand Preference of Male and Female Consumers: From the Perspective of Human Reproductive Motives - Wei, Xia; Huang, Xin; Xie, Yufeng; Tu, Rungting (Frontiers in Psychology, 2022)
Based on the theory of human reproductive motives, this study discusses how erotic stimulation can help activate male and female consumers’ reproductive motives (i.e., mate-attraction and mate-retention motives), influencing product purchase intention and brand personality perception. Specifically, the results of four experiments reveal that when a man receives erotic stimulation from women, his mate-attraction motive is activated. Consequently, he perceives that the brand personality of his possessions is more masculine, and his preference for products with a masculine brand personality is stronger. Unlike male consumers, when a woman receives erotic stimulation from other women, her mate-retention motive is activated. As a result, she perceives that the brand personality of her partner’s possessions is steadier and prefers to purchase products with a steady brand personality for her partner. This effect will not occur when a product is owned by men other than her partner.